2017
DOI: 10.1111/clr.13046
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of narrow diameter implants in posterior jaws: A retrospective study with at least 8‐year follow‐up

Abstract: Objective: The aim of this study was to evaluate the long-term survival, complications, peri-implant conditions, marginal bone loss, and patient satisfaction of fixed dental prostheses supported by narrow diameter implants (NDIs) in the posterior jaws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
75
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(84 citation statements)
references
References 16 publications
6
75
2
1
Order By: Relevance
“…This might explain the significantly higher technical complication rates in SC group. These results corroborate with the study by Shi and colleagues that showed higher percentage of technical complications occurring in SC versus splinted restorations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This might explain the significantly higher technical complication rates in SC group. These results corroborate with the study by Shi and colleagues that showed higher percentage of technical complications occurring in SC versus splinted restorations.…”
Section: Discussionsupporting
confidence: 92%
“…No significant difference in PBL was found between single and splinted crowns ( P = 0.78). This outcome corroborated with a previous clinical studies with 10 and 8‐year follow up . It was reported that the MBL was 1.2 mm in splinted group and 1.3 mm in nonsplinted group at 10‐year examination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are comparable to the overall long‐term survival rate for implant‐supported fixed prostheses reported in previous studies . Shi et al also indicated a similar high survival rate (96.9%) for SDIs in posterior jaws after 10 years.…”
Section: Discussioncontrasting
confidence: 84%
“…(2017) analyzed the implants retrospectively with a start of the measurement after 3 years and reported all losses before 5 years. Also, the other two papers showed a downhill Kaplan–Meier survival rate in relation to follow‐up time (Meyle et al., 2014; Shi et al., 2018). It seems therefore appropriate to conclude that implants do fail over time, although in small numbers.…”
Section: Discussionmentioning
confidence: 99%